DEVELOPMENT, CHARACTERIZATION, EVALUATION AND RELEASE OFSUGARCANE VARIETY 2013 R 81 (CO R 19141) AS RUDRUR CHERUKU-81FOR TELANGANA - G. RAKESH, G.ESWARA REDDY, Y. BHARATHI, M. VIJAYKUMAR, A. DINESH, N. SWAPNA, M. SAI CHARAN, G. NARENDAR, A. KRISHNA CHAITANYA, M. SRIDHAR; B.BALAJI NAIK (The Journal of Research, PJTSAU, 2026)
Sugarcane is one of the most important commercial crops in India, contributing significantly to sugar, jaggery, ethanol and several produces for agro based industries. The present study provides an insight into the development, evaluation and release of 2013R81 (CoR19141) variety which is a mid-late maturing variety released as Rudrur Cheruku-81. The clone originated from the progeny, 81V48 Poly Cross (PC)and developed through the clonal selection at the Regional Sugarcane and Rice Research Station (RS&RRS), Rudrur.The variety was selected and evaluated through sequential stages. Evaluation under station yield trials, the variety recorded a mean cane yield of 131.91 t ha-¹ with anyield advantages of 22.19% and 25.62% over the standard check varieties, Co86032 and CoC671 respectively. The clone exhibited desirable juice quality, with a mean sucrose content of 19.43% and commercial cane sugar (CCS) of 13.45% at 12 months. Initial Varietal Trials conducted under AICRP system of Peninsular Zone, the variety produced a mean cane yield of 127.27 t ha-¹, confirming its wider adaptability and stable performance. Minikittesting proved its superiority under farmers’ field conditions with an average yield advantage of 10.4% over the commercial checks.The variety exhibitedtolerance to biotic stressesand superior jaggeryquality with higher recovery (11.46%) with satisfactory juice quality during post-harvest storage. The comprehensive evaluation revealed that 2013R81 (Rudrur Cheruku-81) combines high cane yield, desirable juice quality, broad adaptation and tolerance to major biotic stresses, making it a promising varietal replacement for enhancing sugarcane productivity and profitability in Telangana.